(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
Psofotopias is an essay that observes how different media, cultural artifacts, and narratives depict dreams and the act of dreaming. I connect these popular media examples to critiques of contemporary technology and media theory, to brain science and philosophy of noise, and I conclude with a commentary on one of my recent art installations. This text is inspired by an interview with Geert Lovink and Ned Rossiter published under the title “Dreamful Computing”, which takes a quote by the late Bernard Stiegler as its prompt: “In order to do politics today, we must dream”. Their overall interest is that of “designing theories that don’t disavow the uncertainty, noise, and contingency of the situation of media”, an interest that I align with in refusing the often clear-cut separation of dreams and nightmares into either utopias or dystopias. By treating dreams with moral indeterminacy, a space for interpretation, analogy, and (trans)individuation is opened up. This space of ambiguity and uncertainty is what I call a “psofotopia”. Psofotopia is a portmanteau (psofos, noise; topos, place) that allows me to argue that dreams, with their cognitive, interpretive, and affective ambiguity, are “spaces of noise” that offer a model to deal with complexity. The dreaming, and its hallucinatory qualities, produces a para-conceptual and para-real psofotopia, a space that triggers collisions and clashes between the immaterial and the physical. An analogy can be drawn between the para-reality of dreams and that of the virtual space, initially imagined by cyberpunk authors as a consensual hallucination that would free humans from their bodily constraints, and eventually developed into an expensive technological infrastructure that aims to perpetuate interpassivity. I will conclude with a discussion about my new work, NNNV XR, an expanded dream that utilizes VR in combination with a sound installation and custom-made transducing furniture producing haptic signals. The installation connects the virtual and the physical world, allowing the experiencer to dream along my dreams. By navigating the sensorial inputs of NNNV XR, the experiencer inhabits the multimedia psofotopia I propose while being aware of the threads that connect the immaterial and the tangible through the para-real.